Pengaruh Brand Ambassador, Brand Image dan Kehalalan Produk Skincare Terhadap Minat Beli Mahasiswi Universitas Sunan Giri Surabaya - Rahmawati, Devi Sinta; Chasanah, Uswatun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Purchase interest is consumer behavior where consumers have a desire to choose and consume a product. As an Indonesian society whose majority population is Muslim, it is obligatory to know the halal and haram of a product to be consumed, especially in the beauty/skincare sector. Therefore, this study aims to determine which one influences consumers, especially female students, more towards purchase interest. Do female students see it in terms of Brand Ambassador, Brand Image or see it in terms of the Halalness of the skincare product. In this study, the approach taken by the researcher is quantitative research and uses statistical formulas to be able to analyze the data and facts obtained. With samples taken from female students of Sunan Giri University Surabaya as many as 85 respondents using probability sampling techniques, namely random sampling techniques distributed via google form. The results of data processing carried out by the researcher are that Brand Image and Brand Ambassador have a more significant influence on purchase interest. While the halalness of skincare products does not affect purchase interest